2018
DOI: 10.1002/jcb.27591
|View full text |Cite
|
Sign up to set email alerts
|

Zellweger spectrum disorder patient–derived fibroblasts with the PEX1‐Gly843Asp allele recover peroxisome functions in response to flavonoids

Abstract: Zellweger spectrum disorder (ZSD) results from biallelic mutations in PEX genes required for peroxisome biogenesis. PEX1-G843D is a common hypomorphic allele in the patient population that is associated with milder disease. In prior work using a PEX1-G843D/null patient fibroblast line expressing a green fluorescent protein (GFP) reporter with a peroxisome-targeting signal (GFP-PTS1), we demonstrated that treatments with the chemical chaperone betaine and flavonoid acacetin diacetate recovered peroxisome functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 52 publications
(107 reference statements)
0
15
0
Order By: Relevance
“…To do the HTS, PEX1G843D fibroblasts and WT fibroblasts were treated either with 25 μM of each compound from the library or with 0.4% vehicle (DMSO). As a positive control, fibroblasts were treated with 100 mM betaine, a compound previously reported to increase peroxisome number in PEX1G843D fibroblasts ( MacLean et al, 2019 ). After 3 days, we performed indirect immunofluorescence (IF) microscopy using an antibody against the C-terminal Peroxisome Targeting Sequence Type 1 Ser-Lys-Leu (SKL), the canonical marker for peroxisomal matrix proteins ( Szilard et al, 1995 ).…”
Section: Resultsmentioning
confidence: 99%
“…To do the HTS, PEX1G843D fibroblasts and WT fibroblasts were treated either with 25 μM of each compound from the library or with 0.4% vehicle (DMSO). As a positive control, fibroblasts were treated with 100 mM betaine, a compound previously reported to increase peroxisome number in PEX1G843D fibroblasts ( MacLean et al, 2019 ). After 3 days, we performed indirect immunofluorescence (IF) microscopy using an antibody against the C-terminal Peroxisome Targeting Sequence Type 1 Ser-Lys-Leu (SKL), the canonical marker for peroxisomal matrix proteins ( Szilard et al, 1995 ).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, there is currently no known effective treatment for ZSDs, the value of genetic diagnosis is limited to prognostic estimation and prenatal genetic diagnosis for future pregnancies in the same family (19). However, the identification of temperature-sensitive peroxisomal defects in p.G843D fibroblasts has suggested that increased protein instability is among the underlying mechanisms for ZSD (20), and indeed there are evolving in vitro evidence showing that ZSDs could benefit from chaperone therapy that rescues molecular misfolding (11,21). It was proposed that ZSDs due to mutated PEX1 might benefit differently from molecular stabilizing treatment due to variations in each mutation's actual functional impairment (12).…”
Section: Discussionmentioning
confidence: 99%
“…It displays a rather mild clinical phenotype, which might be caused by a partial misfolding of the protein [20,21]. Therefore, it has been demonstrated before that Pex1(G843D) cells can recover Pex1(G843D)-, Pex6-and Pex5-protein levels when they are treated with chaperone-like small molecules or by lowering the incubation temperature [21][22][23]. However, because of the residual activity of the point mutant Pex1(G843D), which has been estimated to achieve ca.…”
Section: Discussionmentioning
confidence: 99%